Enhancement Interest in Learning Mathematics for Children with Physical Disabilities at The Legs Using Wheelchair Playing and Learning - Ayu Rahman Hidayah; Putri Aourah; Ade Suci Ramadhani (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
The current educational phenomenon is the large number of children with physical disabilities at the legs. One the reason is the environment that does not provide opportunities for them to grow and develop with their conditions. Conducive and pleasant educational environment for children with physical disabilities at the legs in grades 2 and 3 of elementary school can create a better psychological condition with a sense of enthusiasm and interest to improve academic understanding of mathematics learning. Kuda Baja or Wheelchair Playing and Learning presents as a form of author's effort to overcome these problems. The author prepare this article is using the method of literature study. So in this article Kuda Baja as a wheelchair at once includes learning media with a playing method. There are two-dimentional figure puzzle, stacking numbers, abacus, napier bar tables, and is equipped with a whiteboard and a smartphone stand.